Increasing Community Awareness of the Importance of Mental Health in Lambara Subdistrict Tawaeli District - Utami, Indah Kurnia; Rakanita, Yasinta; Israh; Rusdi, Grasela (Bakti Cendana, 2026)
Mental disorders are illnesses that affect the emotions, thought patterns, and behaviors of those who suffer from them. The limited understanding of the public regarding the causes of mental disorders creates stigma, leading to mental disorders often being associated with supernatural disturbances. This indicates that the mental health literacy of the community is still relatively low. One of the causes of the increase in mental health disorders is the neglect of the signs and symptoms of mental health issues. The purpose of this activity is to increase public understanding of the signs and symptoms of mental disorders. The method used involves direct socialization by the speaker using leaflet brochures and a question-and-answer session. At the beginning and end of the activity, the presenter asked questions related to mental health to gauge the community's understanding. This activity took place in the temporary shelter of Lambara Village, Tawaeli District, attended by the local community. The result of this activity showed an increase in community understanding through pretest and posttest score about 40%. It can be concluded that this activity is very beneficial for the people of Lambara Village